PERANCANGAN ALAT KEAMANAN RUKO MENGGUNAKAN RASPBERRY PI PADA PINTU DAN MONITORING MELALUI SMARTPHONE ALDO AS 8 - alfian junaidi (Lembaga Penelitian Universitas Balikpapan, 2019)
The more crowded the composition of the population at this time makes the needs of the people to be very high both primary needs and secondary needs, because the problem needs increasingly complex then make some people look for a shortcut to fulfill The criminal action is even accompanied by violent acts. The frequent criminal act is theft, because it is the easiest and most fast way to meet the demands of urgent needs.The problem in the background above is how to build a security system that can be monitored easily and automatically, therefore the author chooses a system using a Raspberry Pi because the size of the device is small and High compatibility. After the design of the completion tool can be concluded that the tool goes well, easy to use and can be used for monitoring well